2021
DOI: 10.3168/jds.2021-20342
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Western Canadian dairy farmers on providing outdoor access for dairy cows

Abstract: Dairy cows are highly motivated to access pasture, especially at night in summer. When pasture is not available, dairy cows show a partial preference for alternative types of outdoor access, spending half the night outside in summer on an outdoor sand or wood chip pack. However, many dairy farms do not provide cows outside access. To better understand reasons why dairy farmers choose to provide or not provide outdoor access, we studied the perspectives of dairy farmers located in the 4 Western Canadian provinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 47 publications
4
20
0
Order By: Relevance
“…Respondents who operate a system involving grazing, as opposed to an indoor system, and respondents who had spent longer in farming were significantly more likely to agree, and respondents with higher yields were significantly more likely to disagree. This accords with finding with German [ 30 ], Danish [ 31 ] and Canadian [ 32 ] farmers, that people whose system involved grazing were more likely to have more positive attitudes towards grazing. The result of the model that farmers who have spent longer in farming are more likely to agree that cows should have access to pasture accords with the findings of the cluster analysis.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Respondents who operate a system involving grazing, as opposed to an indoor system, and respondents who had spent longer in farming were significantly more likely to agree, and respondents with higher yields were significantly more likely to disagree. This accords with finding with German [ 30 ], Danish [ 31 ] and Canadian [ 32 ] farmers, that people whose system involved grazing were more likely to have more positive attitudes towards grazing. The result of the model that farmers who have spent longer in farming are more likely to agree that cows should have access to pasture accords with the findings of the cluster analysis.…”
Section: Resultssupporting
confidence: 90%
“…Farmers who operated a system involving grazing were significantly more likely to strongly agree or agree with the statement. This accords with research that farmers are more likely to endorse the benefits of the system they operate [ 29 32 ].…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…For example, Danish research found that farmers have different views on the impact of grazing on milk yield, with non-grazing farmers associating it with lower yields and seeing this as an obstacle to increased grazing, despite a poor relationship between milk yield per cow and profit [Kristensen et al, 2010, cited in [70]]. Qualitative research on farmers in Western Canada shows the impact of farm specific aspects on farmers' attitudes towards outdoor access (as opposed to grazing per se) as well as their personal beliefs and values [81]. They found that reasons not to provide outdoor access related to five main thematic areas: (1) adverse climate conditions; (2) concerns about cow welfare; (3) concerns about profitability; (4) lack of suitable farm infrastructure; and (5) ease of management with indoor systems.…”
Section: Feeding 421 Dairy Cow Feedingmentioning
confidence: 99%